(untitled) (UNED Research Journal, 2019)
Introduction: Chlorothalonil can be determined by several analytical techniques, including gas chromatography (GC) and high performance liquid chromatography (HPLC). These two techniques are used often because they have a higher level of stability and sensitivity. Objective: To compare the efficacy of analytical methodologies by GC and by HPLC for the determination of chlorothalonil in a commercial fungicide. Methods: both the HPLC method and the GC method used by the laboratory were applied to equivalent samples and the results were compared with paired statistical tests. Results: both methods produced statistically equivalent and reliable results. These parameters were satisfactory: selectivity, range of work and linearity, limit of detection and quantification, repeatability, intermediate precision, robustness, veracity and bias; we consider them linear, precise and exact methods that meet the norms of the Costa Rican Accreditation Entity (ECA). Conclusions: both methods for determining chlorothalonil can be used reliably under the defined conditions.